CURRENT RESEARCH ON PUBLIC MANAGEMENT OF NON-FINANCIAL REPORTING OF ENTERPRISES: TRENDS AND PROSPECTS - TANTSIURA, Denys (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article discusses the challenges of public administration regarding non-financial reporting for enterprises in Ukraine, particularly in light of the country’s integration into the European legal framework and the implementation of the Sustainable Development Concept. It examines various organizational, managerial, and legal aspects of regulating non-financial reporting, specifically focusing on Ukraine’s adoption of the EU Corporate Sustainability Reporting Directive (CSRD) and its influence on the establishment of reporting standards within the national business environment. The article analyzes different scientific perspectives on the definition and historical development of non-financial reporting, as well as its key implementation principles. It notes that domestic research primarily emphasizes the economic, accounting, and social dimensions of non-financial reporting, while the aspect of public administration in this area is still underexplored. The theoretical foundation of this study draws on the work of domestic scholars who have investigated the historical evolution of non-financial reporting, its theoretical and practical principles, as well as its essence and content. The study also focuses on the development of methodological tools and identifying effective measures for implementation. The article highlights that the increasing interest among researchers in this topic stems from rapid changes in the socio-political landscape of the country and global economic trends. These changes necessitate the organization of existing scientific knowledge and a reevaluation of both non-financial reporting as a phenomenon and the state’s role in its practical implementation. The necessity of improving public administration efficiency in the processes of collecting, systematizing, and disclosing non-financial information is thoroughly established. The article emphasizes the importance of implementing digital platforms to automate reporting and aligning Ukrainian legislation with European standards. It identifies five key trends and prospects for enhancing public administration in non-financial reporting: a) adapting legislation to EU requirements, b) strengthening state control, c) digitalization and automation of reporting, d) expanding ESG (Environmental, Social, and Governance) regulation practices, and e) increasing the role of the state in promoting non-financial reporting. The research findings underscore the growing significance of public administration in implementing sustainable development standards, which will enhance business transparency, facilitate Ukraine’s integration into the international market, and ensure sustainable economic development.